2013
DOI: 10.2903/j.efsa.2013.3135
|View full text |Cite
|
Sign up to set email alerts
|

Scientific Opinion on an application from Pioneer Hi‐Bred International and Dow AgroSciences LLC (EFSA‐GMO‐NL‐2005‐23) for placing on the market of genetically modified maize 59122 for food and feed uses, import, processing and cultivation under Regulation (EC) No 1829/2003

Abstract: This Scientific Opinion reports on a risk assessment on an application for placing on the market of genetically modified maize 59122 for import and processing for food and feed uses and cultivation. The EFSA GMO Panel considers that maize 59122 is unlikely to have any adverse effect on the environment, except for the possible evolution of resistance to the Cry34Ab1/Cry35Ab1 proteins in coleopteran target pests. The Panel recommends the implementation of appropriate and diversified insect resistance management … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 388 publications
(630 reference statements)
1
7
0
Order By: Relevance
“…Due to the lack of seed germination studies, it was not possible to assess if the observed differences were related to a different germination capacity of the starting materials. A reduction in early stand count was also identified in the agronomic and phenotypic field trials performed during the comparative assessment of two events of the five-event stack maize, namely maize 59122 and GA21 (EFSA, 2007b;EFSA GMO Panel, 2013). The differences observed suggested a lower fitness of the five-event stack maize than that of its conventional counterpart (i.e.…”
Section: Persistence and Invasiveness Of The Gm Plant 32mentioning
confidence: 84%
See 2 more Smart Citations
“…Due to the lack of seed germination studies, it was not possible to assess if the observed differences were related to a different germination capacity of the starting materials. A reduction in early stand count was also identified in the agronomic and phenotypic field trials performed during the comparative assessment of two events of the five-event stack maize, namely maize 59122 and GA21 (EFSA, 2007b;EFSA GMO Panel, 2013). The differences observed suggested a lower fitness of the five-event stack maize than that of its conventional counterpart (i.e.…”
Section: Persistence and Invasiveness Of The Gm Plant 32mentioning
confidence: 84%
“…Since the publication of the scientific opinions on the single maize events by the EFSA GMO Panel (EFSA, 2004(EFSA, , 2005a(EFSA, , 2007b(EFSA, , 2009bEFSA GMO Panel, 2013), no safety issue pertaining to the five single events has been reported by the applicant.…”
Section: Updated Information On Single Eventsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the data provided, it can be concluded that the sequence differences found in maize event DAS-59122-7 in 2016 were already present in the original material used in the risk assessment process (EFSA, 2007(EFSA, , 2008(EFSA, , 2009aEFSA GMO Panel, 2010a, 2013, 2016. Furthermore, the differences identified are located outside the coding sequences of the newly expressed proteins Cry34Ab1, Cry35Ab1 and PAT; two nucleotides are in the TA peroxidase promoter of the cry35Ab1 expression cassette and one nucleotide is in the 5 0 genomic flanking region.…”
Section: Assessmentmentioning
confidence: 97%
“…Evaluation of the systematic search and evaluation of literature Ten of the 11 relevant primary research studies identified by the applicant have already been assessed by the GMO Panel (EFSA GMO Panel, 2013) and it was concluded that none of them raised any safety concerns. The GMO Panel assessed the remaining publication, Ferreira et al (2015), in which it was reported that the agronomic and phenotypic characteristics and nutritional composition of grains and forage of maize 59122 did not differ from its non-GM comparator.…”
Section: 2mentioning
confidence: 99%